1988
DOI: 10.1111/j.1749-6632.1988.tb31867.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Therapy of Early European Lyme Borreliosis and Acrodermatitis Chronica Atrophicans

Abstract: In a study on 121 consecutive patients with erythema migrans, 65 patients obtained oral penicillin, 36 tetracyclines, and 20 amoxicillin-clavulanic-acid. Follow-up was carried out for a median of 29, 17, and 7 months, respectively. In another limited trial on 29 patients with acrodermatitis chronica atrophicans (ACA), 14 patients received oral penicillin, 9 parenteral penicillin, and 6 tetracyclines. There was no statistically significant difference among treatment groups in both therapeutic trials, with the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0
3

Year Published

1992
1992
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 15 publications
2
29
0
3
Order By: Relevance
“…From 10-20% of such patients have persistent or intermittent subjective symptoms of mild to moderate intensity 12 months after completion of therapy ( Table 4). The most common postLyme disease symptoms are fatigue, arthralgias, myalgias, headache, neck stiffness, paresthesias, sleeplessness, irritability, and difficulty with memory, word finding, and concentration [12,13,[25][26][27][28]. The appearance of post-Lyme disease symptoms seems to correlate with disseminated disease, a greater severity of illness at presentation, and delayed antibiotic therapy [12,[29][30][31][32][33]; but not with the duration of the initial antibiotic therapy [13,23].…”
Section: Post-lyme Disease Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…From 10-20% of such patients have persistent or intermittent subjective symptoms of mild to moderate intensity 12 months after completion of therapy ( Table 4). The most common postLyme disease symptoms are fatigue, arthralgias, myalgias, headache, neck stiffness, paresthesias, sleeplessness, irritability, and difficulty with memory, word finding, and concentration [12,13,[25][26][27][28]. The appearance of post-Lyme disease symptoms seems to correlate with disseminated disease, a greater severity of illness at presentation, and delayed antibiotic therapy [12,[29][30][31][32][33]; but not with the duration of the initial antibiotic therapy [13,23].…”
Section: Post-lyme Disease Syndromementioning
confidence: 99%
“…A review of the earliest studies of patients with Lyme disease demonstrate the uncertainty that surrounded the disease and explain in part some of the confusion regarding "chronic Lyme disease". During those initial years, nonspecific symptoms were classified as part of "minor" late manifestations or complications of Lyme disease, to differentiate from the "major" manifestations, which included arthritis, meningoencephalitis and carditis [25,[29][30][31]. In some cases, facial palsy and brief episodes of arthritis were grouped together with nonspecific symptoms as part of minor manifestations of late Lyme disease [29,30], and, in some studies, all patients were grouped together [29,31].…”
Section: The Possible Causes Of Post-lyme Disease Symptomsmentioning
confidence: 99%
“…Decline of IgG and particularly IgM antibody titers was found in many patients, but time to decline in titers was variable and unpredictable. [26][27][28][29][30]34,35 Second, IgG and IgM titers may persist after adequate therapy. [26][27][28][29][30][31][32][33]35 Other patients remain seronegative throughout follow-up.…”
Section: Commentmentioning
confidence: 99%
“…[26][27][28][29][30]34,35 Second, IgG and IgM titers may persist after adequate therapy. [26][27][28][29][30][31][32][33]35 Other patients remain seronegative throughout follow-up. 10,14,29,[34][35][36] Finally, it was described that antibody titers may develop for the first time or even rise during or after therapy.…”
Section: Commentmentioning
confidence: 99%
“…However, no study has clearly defined the optimal treatment with these antibacterial agents, and treatment failures have been reported (4,9,23,25). In addition, Dattwyler et al (12) reported that patients treated with tetracycline, penicillin, and erythromycin during early disease may become seronegative and still develop late Lyme disease.…”
mentioning
confidence: 99%